Innovative technique for the study of pneumoperitoneum in the evaluation of abdominal pain after chemical irritation with zymozan Técnica original para o estudo da influência do pneumoperitônio na avaliação da intensidade da dor abdominal após irritação química com zimozan - Eduardo Crema; Bruna Ferrante Silva; Pauliana Lamounier e Silva; Virmondes Rodrigues Júnior; Fernando Cunha (Acta Cirúrgica Brasileira, 2008)
PURPOSE: To assess the influence of pneumoperitoneum in mice submitted to peritoneal irritation provoked by the biological agent Saccharomyces cerevisae, by counting the number of abdominal contractions elicited. METHODS: To study the effects of pneumoperitoneum analgesic action, 60 mice were divided into two groups: the experimental group, subjected to pneumoperitoneum; and the control group, without pneumoperitoneum. The both groups received intraperitoneal injection of zymosan at a dose of 1mg/0,2ml/mouse. RESULTS: The sum of the number of abdominal contractions of the experimental group (with pneumoperitoneum) was significantly lower than that of the control group (without pneumoperitoneum). In the experimental group, a lower number of contractions occurred in each min compared to the control. CONCLUSION: The observation of the analgesic effect of pneumoperitoneum using CO2 in mice submitted to peritoneal irritation by zymosan was verified. OBJETIVO: Avaliar a influência do pneumoperitônio em animais submetidos à irritação peritoneal provocada pelo agente biológico Saccharomyces cerevisae mediante a contagem do número de contrações abdominais. MÉTODOS: Para o estudo do efeito da ação analgésica do pneumoperitônio os 60 camundongos foram divididos em dois grupos, grupo experimento (com pneumoperitôneo) e controle (sem pneumoperitôneo). Os dois grupos receberam injeção intraperitoneal de zimosan na dose de 1mg/0,2ml/camundongo. RESULTADOS: O somatório do número de contrações abdominais do grupo experimento (com pneumoperitôneo) foi significativamente menor que no grupo controle (sem pneumoperitôneo). O número médio de contrações no grupo controle foi significativamente maior quando comparado com o grupo experimento. CONCLUSÃO: Observou-se efeito analgésico do pneumoperitônio com CO2 em animais submetidos à irritação peritoneal pelo zimosan.